1972
DOI: 10.1111/j.1471-0528.1972.tb15787.x
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Deficiency and Abrupt10 Placentae

Abstract: In a prospective study of 2949 singleton pregnancies of whom one-third were treated with folic acid, the maternal serum folate concentration was assayed at booking and at 30 weeks gestation. No association was found between a low serum folate level and abruptio placentae either in the index pregnancy or in previous pregnancies, and folic acid therapy did not reduce the incidence of abruptio placentae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…A meta-analysis reported a pooled odds ratio of 25.9 (95% CI 0.9–736.3) for abruption in relation to folate deficiency (Ray and Laskin 1999). Our study suggests that low folate levels are not a phenomenon that accompanies women with placental abruption—an observation that provides corroboration with some earlier reports (Alperin et al 1969; Hall 1972; Menon et al 1966; Whalley et al 1969). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A meta-analysis reported a pooled odds ratio of 25.9 (95% CI 0.9–736.3) for abruption in relation to folate deficiency (Ray and Laskin 1999). Our study suggests that low folate levels are not a phenomenon that accompanies women with placental abruption—an observation that provides corroboration with some earlier reports (Alperin et al 1969; Hall 1972; Menon et al 1966; Whalley et al 1969). …”
Section: Discussionsupporting
confidence: 93%
“…Although some studies show increased risk of placental abruption among folate-deficient women (Hibbard 1964, 1975; Hibbard and Hibbard 1963; Ray and Laskin 1999; Streiff and Little 1967), others do not (Alperin et al 1969; Hall 1972; Menon et al 1966; Whalley et al 1969). Moreover, the mechanisms that underlie this association also remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…An abnormal FIGLU test recurred in 73% of 200 women, including 18 of 27 retested in the first trimester. By contrast, Hall (1972) found no association between folate deficiency at first booking or at 30 weeks and placental abruption. Giles (1966) reported 335 cases of megaloblastic anaemia of pregnancy and the puerperium with no significant increase in fetal malformation rate.…”
Section: Discussionmentioning
confidence: 64%
“…Measuring serum and red cell folate levels, most investigators have found no relation between low levels and the occurrence of abruptio placentae (Alpern et al, 1969;Hall, 1972;Whalley et ai., 1969). One study reported that 100% of abruptio placentae patients had low red cell folate levels, while none of the normal delivery patients had low levels (Streiff and Little, 1967).…”
Section: Folatementioning
confidence: 97%